PERANCANGAN STRATEGI PENJUALAN BERDASARKAN SEGMENTASI PELANGGAN DAN COMPLEX PROPORTIONAL ASSESSMENT PADA UMKM JUICEYO - Yulia Ariyanti (2023)
Along with the times and technology, business competition is increasing. JUICEYO MSME, as a fruit juice seller, needs to build customer relationship management to increase customer loyalty. JUICEYO has a problem, namely stagnant income due to the design of marketing strategies that have not adjusted customer characteristics. For this reason, this study aims to determine customer behavior through customer segmentation and design a customer strategy for JUICEYO MSMEs. The K-Means Clustering method is used to group customers into clusters based on Recency, Frequency, and Monetary (RFM) variables. Customer Lifetime Value (CLV) method to determine the value of customer loyalty based on cluster characteristics. Each cluster will be designed development strategy with prioritization using Complex Proportional Assessment (COPRAS). Three customer clusters were obtained, with the results of the CLV calculation for cluster 1 being 1,8748, cluster 2 being 1,8647, and cluster 3 being -0,4032, indicating that cluster 1 is the most profitable customer group. Three strategies are prioritized based on the characteristics of each cluster formed with the aim that the company can focus more on some more effective strategies according to customer characteristics. The strategies of frequency reward program, bundling product, and membership program are the priority strategies recommended for cluster 1, while for cluster 2 and cluster 3 the priority strategies recommended are frequency reward program, bundling product, and content marketing.